Lessons in Chemistry: : A Novel (Random House Large Print, Knopf Doubleday Publishing Group, Books on Tape, Doubleday, 2022)
"Set in 1960s California, this blockbuster debut is the hilarious, idiosyncratic and uplifting story of a female scientist whose career is constantly derailed by the idea that a woman's place is in the home, only to find herself starring as the host of America's most beloved TV cooking show. Elizabeth Zott is not your average woman. In fact Elizabeth Zott would be the first to point out that there is no such thing as an average woman. But it's the 1960s and despite the fact that she is a scientist, her peers are very unscientific when it comes to equality. The only good thing to happen to her on the road to professional fulfillment is a run-in with her super-star colleague Calvin Evans (well, she stole his beakers). The only man who ever treated her--and her ideas--as equal, Calvin is already a legend and Nobel nominee. He's also awkward, kind and tenacious. Theirs is true chemistry. But as events are never as predictable as chemical reactions, three years later Elizabeth Zott is an unwed, single mother (did we mention it's the early 60s??) and the star of America's most beloved cooking show Supper at Six. Elizabeth's singular approach to cooking ('take one pint of H2O and add a pinch of sodium chloride') and independent example are proving revolutionary. Because Elizabeth isn't just teaching women how to cook, she's teaching them how to change the status quo. Laugh-out-loud funny, shrewdly observant, and studded with a dazzling cast of supporting characters, Lessons in Chemistry is as original and vibrant as its protagonist"--